2019
DOI: 10.1186/s13643-019-1195-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic and surgical therapies for patients with Meniere’s disease: a protocol for a systematic review and meta-analysis

Abstract: BackgroundHearing loss is one of the leading causes of disability in Canada and worldwide, with more than one million Canadians enduring a hearing-related disability. Meniere’s disease (MD) is a chronic condition of the inner ear, manifesting as a triad of disabling symptoms, including attacks of vertigo, fluctuating sensorineural hearing loss (SNHL), and tinnitus. Impacts on quality of life are severe, particularly with respect to restrictions in social participation and physical activity, fatigue, and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our review adhered to methods recommended by the Cochrane Collaboration for the conduct of systematic reviews of interventions [12], and conformed to reporting standards of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Network Meta-Analyses (PRISMA-NMA) [13]. We registered the review with the International Prospective Register of Systematic Reviews (PROSPERO; registration #CRD42019119129) [14] and published the review protocol [15]. Minor deviations from the planned protocol were encountered during the review and are detailed in S1 Text.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review adhered to methods recommended by the Cochrane Collaboration for the conduct of systematic reviews of interventions [12], and conformed to reporting standards of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Network Meta-Analyses (PRISMA-NMA) [13]. We registered the review with the International Prospective Register of Systematic Reviews (PROSPERO; registration #CRD42019119129) [14] and published the review protocol [15]. Minor deviations from the planned protocol were encountered during the review and are detailed in S1 Text.…”
Section: Methodsmentioning
confidence: 99%
“…The study’s research question and eligibility criteria with regard to the PICOTS (Population, Intervention, Comparator, Outcomes, Timing, Study design) framework were established a prior and reported in the published protocol [ 15 ], and are also detailed in SA1 Table in S3 Text . In brief, a RCT or quasi-RCT was to be included if it compared pharmacological or surgical interventions of interest to placebo or other active arms for treatment of patients with MD defined as per the established criteria (i.e., American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) 1985, AAO-HNS 1995, and American Academy of Ophthalmology and Otolaryngology (AAOO) 1972) [ 9 , 22 ], and reported a minimum follow-up time of six months post-treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewers will develop a comprehensive data extraction form on Microsoft Excel, as guided by Covidence's piloting forms, and data collection forms for RCTs by Cochrane Training, in addition to several peer-reviewed systematic reviews and protocols [36][37][38][39][40][41]. An initial calibration test will be conducted (AAA, SKS) on a set of 5 randomly selected articles and 5 randomly selected clinical trials to ensure high inter-rater agreement; the latter will compare manual and automatic data extraction methods (using Extracting Accurate efficacy and safety information from ClinicalTrials.gov, EXACT) [42].…”
Section: Selection and Data Collection Processmentioning
confidence: 99%